The Present Religious Situation in India - Woodburne, Angus Stewart (The journal of religion, 1923)
India is now under the sway of a nationalistic movement which is reflected in the effort to get rid of the more objectionable features of faith and practice, and in some quarters in a proposal to return to the simplicity and sublimity of the Vedas, reinterpreted in modern terms. This spirit finds expression in the demand that Christianity in India be released from foreign control and that the Christian message be interpreted through the imagery and thought-forms that are familiar to the people of the country. The system of caste is coming to be recognized as incompatible with a unitary national life; it must be reduced to a mere symbol or entirely obliterated. National unification is further impeded by the fact that the real lines of cleavage are religious and racial rather than political. The Hindu-Muslim concordat is both artificial and ephemeral, while the chief political remedy employed, namely non-co-operation, is negative rather than constructive. Already Indian leaders are dreaming of a higher religious synthesis, spiritual and universal, uniting the best that there is in Christianity with the best of the indigenous faiths, a synthesis in which Jesus shall be honored as one of the avatars of the Infinite, and one of the world's redeemers along with Buddha, Rama, and Krishna.